Upaya Peningkatan Motivasi dan Prestasi Belajar Matematika Materi Bangun Datar Melalui Model Pembelajaran Student Teams Achievment Divisions di Kelas IV Sekolah Dasar - Ma’ruf Arrizal; Sri Muryaningsih (Universitas Sebelas Maret, 2025)
The background of this study was the low motivation and academic achievement of students in mathematics learning. This research was conducted to improve students' motivation and achievement in mathematics, specifically on the topic of plane shapes, by applying the Student Teams Achievement Divisions (STAD) learning model. This study utilized Classroom Action Research (CAR) based on the model by Kemmis and McTaggart, which was carried out in two cycles, each consisting of two meetings. The subject of this research was the fourth-grade students of SD Negeri 1 Gunungkarang, totaling 24 students, including 13 females and the 11 males. Data were collected using test methods and non-test methods, including observation sheets, questionnaires, and documentation that supported the research process. The data analysis techniques employed in this study included questionnaire results to measure student motivation, test results to assess student understanding, and observation sheets to record the activities of teachers and students. The findings of this study revealed that the use of the Student Teams Achievement Divisions (STAD) model successfully enhanced students learning motivation from 70.5% in the first cycle to 84.5% in the second cycle. Regarding students learning achievement, 60.3% of students achieved mastery in the first cycle, which increased to 83% in the second cycle. Teacher activity reached 84.5% in the first cycle and 90.6% in the second cycle. Student activity reached 69.65% in the first cycle and 83.4% in the second cycle. It can be drawn that the implementation of the Student Teams Achievement Divisions (STAD) model can improve both students motivation and academic achievement in mathematics. The STAD model also helps enhance teacher and student engagement during mathematics learning.Penelitian ini dilatarbelakangi oleh rendahnya motivasi dan prestasi belajar siswa dalam pembelajaran matematika. Penelitian ini dilakukan untuk meningkatkan motivasi dan prestasi belajar siswa dalam pembelajaran matematika, khususnya pada materi bangun datar, dengan menerapkan model pembelajaran Student Teams Achievement Divisions (STAD). Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK) berdasarkan model dari Kemmis dan McTaggart, yang dilaksanakan dalam dua siklus, masing-masing terdiri dari dua pertemuan. Subjek penelitian ini adalah siswa kelas IV SD Negeri 1 Gunungkarang yang berjumlah 24 siswa, terdiri dari 13 siswa perempuan dan 11 siswa laki-laki. Pengumpulan data dilakukan dengan menggunakan metode tes dan non tes, meliputi lembar observasi, angket, dan dokumentasi yang mendukung proses penelitian. Teknik analisis data yang digunakan dalam penelitian ini meliputi hasil kuesioner untuk mengukur motivasi siswa, hasil tes untuk menilai pemahaman siswa, dan lembar observasi untuk mencatat aktivitas guru dan siswa. Temuan dari penelitian ini menunjukkan bahwa penggunaan model Student Teams Achievement Divisions (STAD) berhasil meningkatkan motivasi belajar siswa dari 70,5% pada siklus pertama menjadi 84,5% pada siklus kedua. Mengenai prestasi belajar siswa, 60,3% siswa mencapai ketuntasan pada siklus pertama, yang meningkat menjadi 83% pada siklus kedua. Aktivitas guru mencapai 84,5% pada siklus pertama dan 90,6% pada siklus kedua. Aktivitas siswa mencapai 69,65% pada siklus pertama dan 83,4% pada siklus kedua. Dapat disimpulkan bahwa penerapan model Student Teams Achievement Divisions (STAD) dapat meningkatkan motivasi dan prestasi akademik siswa dalam pelajaran matematika. Model STAD juga membantu meningkatkan keterlibatan guru dan siswa selama pembelajaran matematika.